Metabolomics Approach Reveals Important Glioblastoma Plasma Biomarkers for Tumor Biology - Ferrasi, Adriana C. [UNESP]; Puttini, Ricardo [UNESP]; Galvani, Aline F. [UNESP]; Hamamoto Filho, Pedro T. [UNESP]; Delafiori, Jeany; Argente, Victoria D. [UNESP]; de Oliveira, Arthur N.; Dias-Audibert, Flávia L.; Catharino, Rodrigo R.; Silva, Octavio C. [UNESP]; Zanini, Marco A. [UNESP]; Kurokawa, Gabriel A. [UNESP]; et al. (MDPI, 2023)
Glioblastoma (GB) is the most aggressive and frequent primary malignant tumor of the central nervous system and is associated with poor overall survival even after treatment. To better understand tumor biochemical alterations and broaden the potential targets of GB, this study aimed to evaluate differential plasma biomarkers between GB patients and healthy individuals using metabolomics analysis. Plasma samples from both groups were analyzed via untargeted metabolomics using direct injection with an electrospray ionization source and an LTQ mass spectrometer. GB biomarkers were selected via Partial Least Squares Discriminant and Fold-Change analyses and were identified using tandem mass spectrometry with in silico fragmentation, consultation of metabolomics databases, and a literature search. Seven GB biomarkers were identified, some of which were unprecedented biomarkers for GB, including arginylproline (m/z 294), 5-hydroxymethyluracil (m/z 143), and N-acylphosphatidylethanolamine (m/z 982). Notably, four other metabolites were identified. The roles of all seven metabolites in epigenetic modulation, energy metabolism, protein catabolism or folding processes, and signaling pathways that activate cell proliferation and invasion were elucidated. Overall, the findings of this study highlight new molecular targets to guide future investigations on GB. These molecular targets can also be further evaluated to derive their potential as biomedical analytical tools for peripheral blood samples.
Keywords: 5-hydroxymethyluracil; biomarkers; glioblastoma; metabolomics; NAPE; plasma samples